Los símbolos textiles de la cultura Cacha como recurso de identidad en los niños de la Escuela Fernando Daquilema comunidad Shilpalá parroquia Cacha de la provincia de Chimborazo, cantón Riobamba en el período 2014 - García Veloz, Nataly Fernanda (2016)
This research work was done in the Fernando Daquilema School of the Shilpalá Community, which is located in the Cacha parish, Riobamba canton, Chimborazo province. The research topic was on textile symbols of Cacha culture as a resource of identy in children of Fernando Daquilema School of the Shilpalá Community, Cacha parish, Riobamba canton, Chimborazo province, in the period 2014. The existing problems in the institution were identified, and then information was collected by applying observation sheets and surveys, which have been analyzed and quantified. Afterward, it was reached the appropriate conclusions and recommendation. Therefore it is determined the need to be applied learning techniques, such as learning materials to develop knowledge and identity in the boys and girls, it will give the teacher the possibility to apply learning techniques which allow students to learn more about their culture, at the same time it has allowed to test the hypothesis. It is also evidence that there are similar researches but with different proposals, so this is a cause of interest to teachers at this level of education. Everything is carried out for the benefit of the boys and girls, so that the activity is annexed for implementing inside outside the classroom.